Design for wire + arc additive manufacture: design rules and build orientation selection - Lockett, Helen L.; Ding, Jialuo; Williams, Stewart W.; Martina, Filomeno (Taylor & Francis, 2017)
Wire + Arc Additive Manufacture (WAAM) is an additive manufacturing technology that can produce near net-shape parts layer by layer in an automated manner using welding technology controlled by a robot or CNC machine. WAAM has been shown to produce parts with good structural integrity in a range of materials including titanium, steel and aluminium and has the potential to produce high value structural parts at lower cost with much less waste material and shorter lead times that conventional manufacturing processes. This paper provides an initial set of design rules for WAAM and presents a methodology for build orientation selection for WAAM parts. The paper begins with a comparison between the design requirements and capabilities of WAAM and other additive manufacturing technologies, design guidelines for WAAM are then presented based on experimental work. A methodology to select the most appropriate build orientation for WAAM parts is then presented using a multi attribute decision matrix approach to compare different design alternatives. Two aerospace case study parts are provided to illustrate the methodology.
Keywords: Additive manufacture; Design for manufacture; Aerospace engineering